2021
DOI: 10.3390/ijerph182413327
|View full text |Cite
|
Sign up to set email alerts
|

Unleashing the Potential Role of CSR and Altruistic Values to Foster Pro-Environmental Behavior by Hotel Employees

Abstract: The hotel sector, around the globe, has a bad reputation due to its oversized carbon footprint. Therefore, this sector requires different approaches to improve its environmental management efforts. In this regard, the importance of employees’ pro-environmental behavior (PEB) has been recently discussed to reduce an enterprise’s carbon footprint. Reflecting this, the current work aims to improve PEB of employees as an outcome of corporate social responsibility (CSR) and altruistic values (ALV) in the hotel ente… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 78 publications
0
12
0
1
Order By: Relevance
“…The authors conducted a common latent factor (CLF) test to see if a CLF can explain a sheer amount of total variance (beyond 50%). In this vein, the results showed that no such CLF existed, implying that a CMB issue was not critical in this survey [ 28 ]. Moreover, the authors also noted the standardized regression weights between the two models, a model with no CLF (base-line), and a model with a CLF.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The authors conducted a common latent factor (CLF) test to see if a CLF can explain a sheer amount of total variance (beyond 50%). In this vein, the results showed that no such CLF existed, implying that a CMB issue was not critical in this survey [ 28 ]. Moreover, the authors also noted the standardized regression weights between the two models, a model with no CLF (base-line), and a model with a CLF.…”
Section: Resultsmentioning
confidence: 99%
“…For example, Lee, Kim, Kim and Choi [ 62 ] used this scale to measure the A.V of individuals. In the hospitality context of Pakistan, a recent study by Shao, Mahmood and Han [ 28 ] also employed this the same. For this scale, the employees were asked to rate their perception ratings with regard to importance.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Drawing on P-O fit and social identity theories [ 32 , 40 , 41 ], the present empirical research tested a sequential pathway model explaining how employees’ perceptions of their organization’s environmental CSR practices foster these workers’ voluntary PEBs on the job. This study sought to expand the existing literature on these behaviors by offering new insights into the ways organizations can foster PEBs among their staff members [ 17 , 20 , 21 , 22 , 23 , 31 , 63 ].…”
Section: Discussionmentioning
confidence: 99%
“…PEBs consist of employees’ workplace behaviors that have a beneficial effect on the environment [ 13 , 14 , 15 , 16 , 17 , 18 ], such as turning off lights, saving water, separating materials for recycling, or advocating eco-friendly actions. Individually, PEBs may appear to be of little importance, but, as they spread throughout organizations, these behaviors can have a multiplier effect and contribute to the achievement of sustainability targets [ 10 , 19 ].…”
Section: Introductionmentioning
confidence: 99%